2003
DOI: 10.1021/la030256t
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Chromonic Liquid-Crystalline Phases of Bis-(N,N-diethylaminoethyl)perylene-3,4,9,10-tetracarboxylic Diimide Dihydrochloride by Polarized Optical Microscopy and 2H NMR Spectroscopy

Abstract: The chromonic liquid-crystalline properties of bis-(N,N-diethylaminoethyl)perylene-3,4,9,10-tetracarboxylic diimide dihydrochloride in an aqueous solution were investigated by polarized light microscopy and 2H NMR spectroscopy. Both techniques indicate a narrow I + N biphasic region and a broad N phase region at concentrations ranging from approximately 6.9 to approximately 30 wt % at room temperature. Optical microscopy indicates that a hexagonal M phase exists at higher concentrations. The variation of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 32 publications
4
43
0
2
Order By: Relevance
“…More interestingly, the nematic phase of this PBI (6-7a) could be aligned in films by shearing and after evaporation of the solvent resulting in anisotropically oriented solid films that linearly polarize light with dichroic ratios up to 30, rivaling even some commercial polarizers. 465,466 It is interesting to note that TamChang and co-workers have also reported that a higher homologue of cationic PBI 6-7a, that is, a quaterrylene bisimide bearing diethylammoniumethyl imide substituents with formate counterions, exhibited lyotropic LC properties, and shearinginduced orientation of its nematic phase resulted in highly anisotropically ordered thin solid films, which function as dichroic polarizers of light at long wavelengths. 469,470 A chiral lyotropic liquid crystal based on cationic PBI 6-7f bearing optically active ethylpyrrolidinium chloride groups at the imide positions was reported by Lee and co-workers.…”
Section: Liquid-crystalline Ionic Pbismentioning
confidence: 99%
“…More interestingly, the nematic phase of this PBI (6-7a) could be aligned in films by shearing and after evaporation of the solvent resulting in anisotropically oriented solid films that linearly polarize light with dichroic ratios up to 30, rivaling even some commercial polarizers. 465,466 It is interesting to note that TamChang and co-workers have also reported that a higher homologue of cationic PBI 6-7a, that is, a quaterrylene bisimide bearing diethylammoniumethyl imide substituents with formate counterions, exhibited lyotropic LC properties, and shearinginduced orientation of its nematic phase resulted in highly anisotropically ordered thin solid films, which function as dichroic polarizers of light at long wavelengths. 469,470 A chiral lyotropic liquid crystal based on cationic PBI 6-7f bearing optically active ethylpyrrolidinium chloride groups at the imide positions was reported by Lee and co-workers.…”
Section: Liquid-crystalline Ionic Pbismentioning
confidence: 99%
“…Following the early works of Dryer [18], different research groups have explored the possibility of using dye-based LCLCs in the fabrication of polarizing [19][20][21][22][23][24][25][26] and optical compensating elements [27,28]. The main feature allowing such an application is that when water evaporates, the resulting dry film still preserves an orientational order and thus anisotropic optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2 a, the 2 H NMR spectra of 1 a (2.0 wt % in 2 H 2 O) at temperatures below 31 8C show two sharp peaks, indicating that the 2 H nucleus is in an anisotropic environment, that is, an aligned chromonic nematic (N) phase upon exposure to the NMR magnetic field. [10] When the sample was allowed to warm up from 31 to 35 8C, a singlet in the middle of the doublet peaks gradually emerged at the expense of the doublet intensity. At 35 8C, only the singlet signal remained.…”
mentioning
confidence: 99%